Classification of the Projective Line over Galois Field of Order 31 - Al-Seraji , Najm Abdulzahra Makhrib; Essa, Ahmed Khallaf (Iraqi Journal of Science, 2023)
Our research is related to the projective line over the finite field, in this paper, the main purpose is to classify the sets of size K on the projective line PG (1,31), where K = 3,…,7 the number of inequivalent K-set with stabilizer group by using the GAP Program is computed.